The Influence of Competitive Positioning and Rivalry on Emerging Market Risk Assessment - McNamara, Gerry; Vaaler, Paul M. (Journal of International Business Studies, 2000)
Rating agencies play a pivotal role in international credit transactions. Their sovereign risk-assessments are largely thought to reflect objective evaluations of the creditworthiness of potential borrowers. We test this assumption by examining the role that competitive positioning and dynamics play in the risk-assessments these agencies provide. Our analyses of agency risk-assessments for emerging-market sovereign borrowers indicate that they are significantly related to agency positioning as an incumbent or insurgent (new entrant), to agency specialization in sovereigns from particular geographic regions, and in some instances, to the level of agency rivalry in a specific sovereign market. Our findings suggest both significant general and contingent links between foreign investment risk-assessment and competitive positioning and rivalry among agencies.